Efflorescence of acquired epidermodysplasia verruciformis due to immune reconstitution inflammatory syndrome-like mechanisms following anti-HPV vaccination in a HIV-positive patient. (January 2022) - Parietti, Michele; Trunfio, Mattia; Delmonte, Sergio; Conti, Luca; Trentalange, Alice; Bonora, Stefano; Calcagno, Andrea; Ribero, Simone
Epidermodysplasia verruciformis (EV) is a rare cutaneous pre-cancerous condition characterized by presence of flat, scaly macules, verruca-like papillomatous papules, seborrheic keratosis-like lesions, and pink-red pityriasis versicolor-like macules. The disease is caused by abnormal susceptibility to certain specific beta-HPV subtypes, most commonly 5 and 8. Classic EV is genetically determined, but in immunocompromised individuals, an acquired form can occur. Only 48 cases of acquired EV (AEV) in people living with HIV have been described. We describe a case of AEV in a 36-year-old HIV-positive man with an history of stable optimal CD4 cell count and undetectable HIV viral load. The AEV significantly deteriorated after the administration of the second dose of the quadrivalent anti-HPV vaccine and did not improve despite local treatment, anti-HPV vaccination completion, and persistently optimal combined antiretroviral treatment adherence. To the best of our knowledge, this is the first report of an AEV deterioration with a clinical and temporal pattern mimicking an immune reconstitution inflammatory syndrome (IRIS) following anti-HPV vaccination, instead of low CD4 count restoration. After reviewing the current literature, we have hypothesized a vaccine-mediated IRIS-like phenomenon in the pathogenesis of the disease.